Mild Hypoxia Enhances the Expression of HIF and VEGF and Triggers the Response to Injury in Rat Kidneys - Xu, Yaya; Kong, Xiangmei; Li, Jiru; Cui, Tiantian; Wei, Yifan; Xu, Jiayue; Zhu, Yueniu; Zhu, Xiaodong (Frontiers in Physiology, 2021)
Background Hypoxia contributes to a cascade of inflammatory response mechanisms in kidneys that result in the development of renal interstitial fibrosis and subsequent chronic renal failure. Nonetheless, the kidney possesses a self-protection mechanism under a certain degree of hypoxia and this mechanism its adaptation to hypoxia. As the hypoxia-inducible factor (HIF)–vascular endothelial growth factor (VEGF) axis is a key pathway for neovascularization, the activation of this axis is a target for renal hypoxia therapies. Methods Sprague–Dawley rats were exposed to normobaric hypoxia and subdivided into three groups, namely group A (21% O2), group B (10% O2), and group C (7% O2). Renal tissue samples were processed and analyzed to determine pathological morphological changes, the expression of HIF, VEGF, inflammation factor and vascular density. Results We found that as the duration of hypoxia increased, destructive changes in the kidney tissues became more severe in group C (7% O2). In contrast, the increased duration of hypoxia did not exacerbate kidney damage in group B (10% O2). As the hypoxia was prolonged and the degree of hypoxia increased, the expression of HIF-1α increased gradually. As hypoxia time increased, the expression of VEGF increased gradually, but VEGF expression in group B (10% O2) was the highest. Group C (7% O2) had higher levels of IL-6, IL-10, and TNF-alpha. Additionally, the highest vascular density was observed in group B. Conclusion These findings suggest that activating the HIF–VEGF signaling pathway to regulate angiogenesis after infliction of hypoxic kidney injury may provide clues for the development of novel CKD treatments.